Relationship Between Santri's Behaviors and Physical Environment with Ari Incidence in Assalafi Al Fithrah Islamic Boarding School Surabaya - Astuti, Nindy Dewi (JURNAL KESEHATAN LINGKUNGAN, 2018)
Pesantren sanitation is associated with infectious diseases, especially acute respiratory infections ( ARI). Bad physical environment could become a suitable environment for the breeding grounds of bacteria and viruses that causes ARI. This study aimed to analyze the relationship between of santri's behavior and physical environments with the incidence of ARI in Al Fithrah Assalafi Islamic Boarding School Surabaya 2015. This research was an analytic observational study with cross sectional method. The population of this study were the female students amounted to 969 people. The sample size in this study was using the simple random sampling proportion estimates method with the Lottery sampling technique so total respondens were 71 students. The relationship between variable was using the X2-test statistical test (chi-square). The results showed that 46 students and there was no relationship between the santri's behavior with ARI. The associated variables with ARI incidence in women students was the physical environment included ventilation, air temperature, and occupancy density. The school manager should give the gauze in the ventilation to change the room air circulation and made a cleaning schedule for the students so they can have a responsibilities of the rooms hygiene.